2017
DOI: 10.1093/mnras/stx077
|View full text |Cite
|
Sign up to set email alerts
|

Three new pulsating sdB stars discovered with SuperWASP

Abstract: We present an analysis of three new pulsating subdwarf B stars discovered in the SuperWASP archive. Two of the stars, J1938+5609 and J0902-0720, are p-mode pulsators; J1938+5609 shows a pulsation at 231.62 d −1 (P = 373 s; 2681 µHz) with an amplitude of 4 mmag, whereas J0902-0720 pulsates at frequencies 636.74 d −1 (P = 136 s; 7370 µHz) and 615.34 d −1 (P = 140 s; 7122 µHz), with amplitudes 7.27 and 1.53 mmag, respectively. The third star, J2344-3427, is a hybrid pulsator with a p-mode frequency at 223.16 d −1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 93 publications
1
34
1
Order By: Relevance
“…In this paper, we have shown that EC 03089−6421 is a very rapid pulsator with two frequencies near 32.1 and 29.2 mHzperiods of 31.1 and 34.2 s, much shorter than observed in the other sdOV stars, or in any pulsating subdwarf (see table 1 of Holdsworth et al 2017). Both frequencies have quite variable amplitudesbetween about 0.2 and 2 per cent on a time-scale of a few days and also varying on a time-scale of hours.…”
Section: Discussionmentioning
confidence: 78%
“…In this paper, we have shown that EC 03089−6421 is a very rapid pulsator with two frequencies near 32.1 and 29.2 mHzperiods of 31.1 and 34.2 s, much shorter than observed in the other sdOV stars, or in any pulsating subdwarf (see table 1 of Holdsworth et al 2017). Both frequencies have quite variable amplitudesbetween about 0.2 and 2 per cent on a time-scale of a few days and also varying on a time-scale of hours.…”
Section: Discussionmentioning
confidence: 78%
“…It also produces excellent data for the study of stellar variability. For full details of the SuperWASP project, see Pollacco et al (2006); for examples of stellar variability studies that have been conducted with the data, we refer the reader to the following papers: Maxted et al (2008); Thomas et al (2010); Norton et al (2011Norton et al ( , 2016; Smalley et al (2011Smalley et al ( , 2014Smalley et al ( , 2017; Holdsworth et al (2014aHoldsworth et al ( , 2017; Bowman et al (2015); Greer et al (2017).…”
Section: Superwasp Datamentioning
confidence: 99%
“…Indeed, many of these projects have been employed for that purpose (e.g. Pepper et al 2008;Hartman et al 2011;Ulaczyk et al 2013;Holdsworth et al 2014a;Smalley et al 2017;Holdsworth et al 2017). The ability of these surveys to achieve mmag precision provides an extensive all-sky database in which to search for low-amplitude stellar variability, which can then be observed at much higher precision by space-based missions such as K2 (Howell et al 2014) and the upcoming Transiting Exoplanet Survey Satellite (TESS; Ricker et al 2015).…”
Section: Introductionmentioning
confidence: 99%